"Do not Stifle the Spirit": The Vision of Yves Congar for Charismatic Ecclesiology. (4th December 2013) - Ebo Annan, Stephen
Abstract The commemoration of the half‐centenary of the Second Vatican Council has garnered enormous interest in the protagonists, circumstances and, interpretations that evolved in the period leading up to and following the council. Beyond the dialectics of hermeneutics of (dis)continuity of the council which has gained currency in recent post‐conciliar discourse, however, attention has equally been drawn to the grand leitmotif that birthed the Council, namely, the clichéd aggiornamento and the pentecostal renewal envisioned by Blessed Pope John XXIII. Despite its determining importance, Cardinal Walter Kasper opines that the Church is still certainly a long way from being able to speak of a new Pentecost. One of the architects of such ecclesial reforms and pneumatological renewal in the Council was the erudite French ecclesiologist and ecumenist Yves Marie Congar (1904–1995). This article seeks to demonstrate that Congar was not only a celebrated pneumatologist but also a visionary of charismatic ecclesiology, deemed as a resourceful tool for re‐evangelization.